If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 = 2x + -4 Reorder the terms: 12 + 3x = 2x + -4 Reorder the terms: 12 + 3x = -4 + 2x Solving 12 + 3x = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 3x + -2x = -4 + 2x + -2x Combine like terms: 3x + -2x = 1x 12 + 1x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 1x = -4 + 0 12 + 1x = -4 Add '-12' to each side of the equation. 12 + -12 + 1x = -4 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = -4 + -12 1x = -4 + -12 Combine like terms: -4 + -12 = -16 1x = -16 Divide each side by '1'. x = -16 Simplifying x = -16
| 0.41x+0.72=0.61x-4.22 | | h+4=30 | | x(2x-8)=(2x+5)(x-6) | | 6y=-17 | | (4x+34)+(7x-10)+(5x+12)=180 | | v^2-3v-40=0 | | 60(10-x)=90 | | 10-3/4x=5 | | -37=-11.9t-4.9t^2 | | 2x-(4x-1)=9 | | x+1+9=3x-24 | | 4.9t^2-125-5.2t=0 | | -2x-13=3x+12 | | 7x+19= | | x+1+9=3-24 | | 5x^4-3x^3-3x^2=0 | | 4-x+2=3x+5 | | 4r-4/8=4r-8/4 | | 46-9x=18+5x | | x/a-5+b | | 6(-7x+3)+2x=1 | | 5y+5.2=2-5y | | (-10*-2)+(2*6)/-2 | | x/3+26=14 | | 5y^2-9x^2-36=0 | | -1=-1.6+-0.8m | | 7*r-7/2 | | x+x+(x+61.5)=180 | | 4(5-3x)= | | -3x=-14+4x | | 8x-52=6x+8 | | -2/3x+53+59 |